W.B. 2 Five Year Plan Revised Draft - Planning Commission (Planning Commission, 1955)
The following pages contain the revised draft of the Second Five- Year Plan for West Bengal submitted to the Planning Commission on December 12. 1955. the original draft of the Plan was discussed with the Planning Commission in September last. the present revised draft was prepared in the light of that discussion within the ceiling of Rs. 161.5 crores fixed by the Planning Commission.
The Institute of Economic Growth